The local-orbifold correspondence for simple normal crossings pairs - Battistella, Luca; Nabijou, Navid; Tseng, Hsian-Hua; You, Fenglong (Arxiv, 2021)
For X a smooth projective variety and D=D1+…+Dn a simple normal crossings divisor, we establish a precise cycle-level correspondence between the genus zero local Gromov-Witten theory of the bundle ⊕ni=1OX(−Di) and the maximal contact Gromov-Witten theory of the multi-root stack XD,r⃗ . The proof is an implementation of the rank reduction strategy. We use this point of view to clarify the relationship between logarithmic and orbifold invariants.
Artikelversion v3 vom 22. Februar 2022
Gesehen am 09.01.2024